Fitness profiles of professional futsal players: identifying age-related differences - Sekulic, D.; Gilic, B.; Foretic, N.; Spasic, M.; Uljevic, O.; Veršic, S. (Biomedical Human Kinetics, 2020)
Study aim: The aim of this study was to determine the fitness profiles of senior and junior futsal players and to identify potential differences between the studied age groups.